1995
DOI: 10.1097/00005373-199512000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Thoracoabdominal Airgun Wounds in a Porcine Model

Abstract: Airguns create serious intracavitary organ injuries in a porcine model. Moreover, ballistic research is possible in unusual surroundings, such as a packing plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Adult pig (Sus scrofa domestica) ribs were utilized in this study; although similar in many ways to human anatomy, porcine anatomy differs in the thickness of the overlying soft tissue (36). Jakiae-Razumoviae et al (37) reported a "full-thickness [of] ventral thoracic skin section" of c. 1.5 cm in humans, while Janda (38) reported a 2.5 cm tissue thickness in the thoracic region; therefore, the average thickness of 2 cm was used as a guideline for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Adult pig (Sus scrofa domestica) ribs were utilized in this study; although similar in many ways to human anatomy, porcine anatomy differs in the thickness of the overlying soft tissue (36). Jakiae-Razumoviae et al (37) reported a "full-thickness [of] ventral thoracic skin section" of c. 1.5 cm in humans, while Janda (38) reported a 2.5 cm tissue thickness in the thoracic region; therefore, the average thickness of 2 cm was used as a guideline for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Along with mass and caliber, the shape of the bullet affects wounding potential as well. Pointed pellets, as used by the victim, perforate skin with smaller velocities and penetrate more deeply than rounded pellets . Apart from metallic pellets and metallic BBs, spherical plastic BBs (6 or 8 mm caliber, weighting between 0.12 and 0.43 g) are used in soft air guns.…”
Section: Discussionmentioning
confidence: 99%
“…The Canadian Medical Association (CMA) and the Canadian Paediatric Society (CPS) have published statements on firearms safety (CMA 2021; CPS 2018) that support classifying non-powdered firearms capable of causing injury as firearms under Canada's Firearms Act (1995). This would involve redefining firearms to include all barrelled weapons with a discharge force and/or velocity capable of causing significant injury, instituting new thresholds for speed and energy that are based on physical science and medical evidence (Kennedy et al 2006;McKenzie et al 1995).…”
Section: Legislation and Safetymentioning
confidence: 99%
“…Because most fire at less than 152.4 metres/second -and with muzzle energy less than 5.7 joules -they are not considered "firearms" under Canada's Firearms Act (1995) and as defined by the Criminal Code (1985). While slower and less forceful than traditional firearms, many of these devices do discharge with speed and force great enough to penetrate skin or a human eye (Kennedy et al 2006;McKenzie et al 1995).…”
Section: Introductionmentioning
confidence: 99%